PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS GAME EDUCAPLAY DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN SKI - Alya Fitriani; Jasiah, Jasiah (Sindoro: Cendikia Pendidikan, 2024)
This study aims to determine the utilization of Educaplay game-based learning media in increasing student learning motivation in SKI learning. The research method used is a type of Research & Development research or development research that aims to create a product and test the effectiveness of the product. The adapted development method is the Dick & Carey method which consists of 10 steps, but the author only applies 9 steps because it adapts to the needs.